Characteristic Behavior of Ion Acoustic Wave in A dusty Plasma - Jassim, M. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research, we make an attempt to derive theoretically 1-D linear dispersion relation of ion-acoustic waves in uniform unmagnetized dusty plasma valid in the long wavelength limits. This equation matched previously special equation of acoustic modes of a general form in magnetized dusty plasma.  Depending on previously mentioned experimental data, we numerically consider various parameters that affect the properties of these waves in   dusty plasma. The study has shown that the presence of dust grains is to modify the properties of ion acoustic waves and affect the behavior of the plasma in which they are immersed.